Design and Optimization of Six-bar Leg-supporter Mechanism - Hu Chong; Huang Songtan; Ying Fuqiang; Duan Lijiang (Jixie chuandong)
For the most of the leg-supporter mechanism of leisure chairs,it can’t run smoothly during the movement and hard to keep working condition etc. Aiming at these problems,a new six-bar leg-supporter mechanism is designed based on the theory of ergonomics,the mathematical model is established. Then the multi-objective optimization of mechanism is carried out by using Insight after the parametric design in ADAMS. According to the optimization results,the model is modified and simulated again,then comparing the data before and after optimization. The results show that after optimization,the new six-bar leg-supporter mechanism can run smoothly and meet the design requirement.